Thong Heng Workshop Appointment System - Gan, Qing Xiang; Rosmamalmi Mat Nawi (Applied Information Technology And Computer Science, 2024)
Thong Heng Workshop Appointment System (THA) is a web-based appointment system that was developed for Thong Heng Motor and Battery Services (Thong Heng) which is a traditional workshop that provides repair services for vehicles. When a large number of clients need auto repairs at once, the shop may not have enough workers to meet their needs. This project is to solve that problem for Thong Heng’s customers as they can make car service appointments online. The project was developed based on the waterfall method by using Visual Studio Code software and the MySQL database. The web-based system will make it easy for Thong Heng to manage car service appointments. The success of the evaluations shows that the appointment system works as intended. It will be easier for Thong Heng to control the number of customers arriving at the workshop.